Enrichment of Marinobacter sp. and Halophilic Homoacetogens at the Biocathode of Microbial Electrosynthesis System Inoculated With Red Sea Brine Pool - Alqahtani, Manal F.; Bajracharya, Suman; Katuri, Krishna P.; Ali, Muhammad; Ragab, Ala’a; Michoud, Grégoire; Daffonchio, Daniele; Saikaly, Pascal E. (Frontiers in Microbiology, 2019)
Homoacetogens are efficient CO2 fixing bacteria using H2 as electron donor to produce acetate. These organisms can be enriched at the biocathode of microbial electrosynthesis (MES) for electricity-driven CO2 reduction to acetate. Studies exploring homoacetogens in MES are mainly conducted using pure or mix-culture anaerobic inocula from samples with standard environmental conditions. Extreme marine environments host unique microbial communities including homoacetogens that may have unique capabilities due to their adaptation to harsh environmental conditions. Anaerobic deep-sea brine pools are hypersaline and metalliferous environments and homoacetogens can be expected to live in these environments due to their remarkable metabolic flexibility and energy-efficient biosynthesis. However, brine pools have never been explored as inocula for the enrichment of homacetogens in MES. Here we used the saline waters from a Red Sea brine pool as inoculum for the enrichment of halophilic homoacetogens at the biocathode (‒1 V vs Ag/AgCl) of MES. Volatile fatty acids, especially acetate, along with hydrogen gas were produced in MES systems operated at 25 and 10% salinity. Acetate concentration increased when MES was operated at a lower salinity 3.5%, representing typical seawater salinity. Amplicon sequencing and genome-centric metagenomics of matured cathodic biofilm showed dominance of the genus Marinobacter and phylum Firmicutes at all tested salinities. Seventeen high-quality draft metagenome-assembled genomes (MAGs) were extracted from the biocathode samples. The recovered MAGs accounted for 874% of the quality filtered sequence reads. Genome analysis of the MAGs suggested CO2 fixation via Wood-Ljundahl pathway by members of the phylym Firmicutes and the fixed CO2 was possibly utilized by Marinobacter sp. for growth by consuming O2 escaping from the anode to the cathode for respiration. The enrichment of Marinobacter sp. with homoacetogens was only possible because of the specific cathodic environment in MES. These findings suggest that in organic carbon-limited saline environments, Marinobacter spp. can live in consortia with CO2 fixing bacteria such as homoacetogens, which can provide them with fixed carbon as a source of carbon and energy.